Recognition and redistribution in multinational federations - Jewkes, Michael; Gregoire, Jean-François (Leuven Univerisity Press, 2015)
Almost without exception, multinational states across the West are facing existential crises precipitated by the resurgence of sub-state national minority groups. This edited volume brings together many of the world's leading theorists of multinational justice in order to analyse two of the most frequent areas of debate and dispute in multinational federations: recognition and redistribution. The authors address questions such as the following: What are the most appropriate forms of institutional recognition for sub-state national groups? How is the concept of redistributive justice affected by the presence of federal institutions and autonomous sub-state nationalities? And what are the potential sources of stability that fractious federations can call upon? As well as extensive theoretical analyses, the book is peppered throughout with examples drawn from actual multinational states including Canada, Belgium, Spain, and the United Kingdom.